2019
DOI: 10.1080/01916122.2019.1596391
|View full text |Cite
|
Sign up to set email alerts
|

A review of the areoligeracean dinoflagellate cystCyclonepheliumand morphologically similar genera

Abstract: A group of mainly Cretaceous areoligeracean dinoflagellate cyst genera, which we call the "Cyclonephelium group", has proved difficult to classify. The group comprises Aptea,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…A;Niechwedowicz and Walaszczyk 2021). This event illustrates the earliest significant radiation of the genus, which otherwise is more typical of the Paleogene (e.g Fensome et al 2016Fensome et al , 2019b…”
mentioning
confidence: 82%
“…A;Niechwedowicz and Walaszczyk 2021). This event illustrates the earliest significant radiation of the genus, which otherwise is more typical of the Paleogene (e.g Fensome et al 2016Fensome et al , 2019b…”
mentioning
confidence: 82%
“…These initial observations revealed that only few taxa have a consistent stratigraphic range in Hole 909C, and abundances of these selected taxa were visually estimated. Taxonomic nomenclature follows Fensome et al (2019). The full names of taxa and abundance estimates are listed in supplementary Table 1.…”
Section: Sampling and Palynological Methodsmentioning
confidence: 99%
“…Subsequent taxonomic revision (Pearce et al, 2003(Pearce et al, , 2011 differentiated two main species of Senoniasphaera in the Turonian: S. turonica (= S. rotundata alveolata of Pearce et al, 2003Pearce et al, , 2009Prince et al, 2008); and S. rotundata (= S. rotundata rotundata), with the former representing the older Turonian species. Recently, S. rotundata rotundata has been reassigned to Canningia glomerata (Fensome et al, 2019b; Fig. 5A).…”
Section: Senoniasphaera Turonica and The S Turonica Subzonementioning
confidence: 99%
“…*Spiniferites twistringiensis(Maier, 1959) Fensome et al, 1990 Turnhosphaera hypoflata(Yun Hyesu, 1981) Slimani, 1994 Subfamily:LEPTODINIOIDEAE Fensome et al, 1993 Kleithriasphaeridium loffrenseDavey and Verdier, 1976 Kleithriasphaeridium mantellii (Davey and Williams 1966a)Fensome et al, 2016b Kleithriasphaeridium readei (Davey andWilliams, 1966b) Davey and Verdier, 1976 *Oligosphaeridium complex (White, 1842) Davey and Williams, 1966b *Oligosphaeridium pulcherrimum (Deflandre and Cookson, 1955) Davey and Williams, 1966a Family: AREOLIGERACEAE Evitt, 1963 Canningia glomerata(Clarke and Verdier, 1967) Fensome et al, 2019b Canningia reticulataCookson and Eisenack, 1960 Canningia spongireticulataPrössl, 1990 Circulodinium distinctum(Deflandre and Cookson, 1955) Jansonius, 1986 Cleistosphaeridium latoaculeum(Yun, 1981) Fensome et al, 2019b *Cyclonephelium membraniphorum Cookson and Eisenack, 1962 Senoniasphaera filoreticulata(Slimani, 1994) Fensome et al, 2019b Senoniasphaera spp Clarke and Verdier, 1967 . *Tenua colliveri (Cookson and Eisenack, 1960) Helby, 1987 Suborder:CERATIINEAE Fensome et al, 1993 Suborder:GONIODOMINEAE Fensome et al, 1993 Family: GONIODOMACEAE Lindemann, 1928 *Hystrichosphaeridium tubiferum subsp.…”
mentioning
confidence: 99%